2016
DOI: 10.1111/ijcp.12810
|View full text |Cite
|
Sign up to set email alerts
|

DCD liver transplant infection: experience from a single centre in China

Abstract: This is the first study that offers detailed data revealing the timing and incidence of bacterial and fungal infection among adult DCD liver transplant recipients. Bacterial and fungal infection occurs at a high rate during the first week after DCD liver transplant, especially in patients with prolonged respiratory support time and renal failure, and infection is related to increased hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
5
10
3
Order By: Relevance
“…In our hospital, the incidence of infection after liver transplantation reached 46.7%. It was consistent with the previous reports studied in China, in which 15%-69% of patients acquired postoperative infection [13][14][15][16][17] . Most infection occurred in the first month after liver transplantation, which is related to surgical complications as for traditional view 18 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our hospital, the incidence of infection after liver transplantation reached 46.7%. It was consistent with the previous reports studied in China, in which 15%-69% of patients acquired postoperative infection [13][14][15][16][17] . Most infection occurred in the first month after liver transplantation, which is related to surgical complications as for traditional view 18 .…”
Section: Discussionsupporting
confidence: 93%
“…However, the most common site of infection is not surgical site, but the respiratory tract and Gram-negative pathogens are major pathogens. Our findings were also supported by other studies in China [14][15] . These indicated that the pattern of posttransplant infection was changed and nosocomial infection might be the most important epidemiological exposure in the first month after transplantation in China.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported by Hamandi et al that infectious complications in solid organ transplants require hospitalisation in 603 of 1414 readmissions at a rate of 0.43 episodes per 1000 transplant-days (95% CI: 0.40-0.47), with 85% occurring after 6 months following transplantation [6]. Conversely, Tu et al report most post-DDLT infections (61.9%) occurring within the first week of transplant, and the 1-and 3-year survival rates without infection significantly increased compared with recipients with infection (p = 0.007) [27]. It is important to know the timings, rate and type of infections after LDLT and DDLT since these infections are not just a controllable risk factor for failure but there has also been a recent quest for markers such as neopterin, associating 1-year posttransplant infections with mortality [28].…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, Tu et al . report most post-DDLT infections (61.9%) occurring within the first week of transplant, and the 1- and 3-year survival rates without infection significantly increased compared with recipients with infection ( p = 0.007) [ 27 ]. It is important to know the timings, rate and type of infections after LDLT and DDLT since these infections are not just a controllable risk factor for failure but there has also been a recent quest for markers such as neopterin, associating 1-year posttransplant infections with mortality [ 28 ].…”
Section: Discussionmentioning
confidence: 99%